AGAMA, MODERNITAS DAN MENTALITAS: Implikasi Konsep Qana’ah Hamka Terhadap Kesehatan Mental (MUHARRIK: Jurnal Dakwah dan Sosial, 2020)
Human life increasingly modern along with the times. However, modernity leads them to become unsafe and uncomfortable living life. Peace of life can only be achieved through the right attitude towards the treasures and sparkles of the other world. This attitude is known as qana'ah, which means feeling sufficient and satisfied for what he has. This study aims to describe the study of qana'ah according to Hamka and to determine its implications in mental health. It is a literature study that using descriptive qualitative methods. The results of this study indicate that qana'ah according to Hamka is an attitude that accepts what it is, but still must make the effort. Qana'ah requires the sincerity of the heart in accepting what is owned by accompanied by maximum effort. If someone practices the concept of qana'ah Hamka, then a healthy mental will be formed. The application of qana'ah in daily life can make a person always optimistic, never give up and not greedy in everything. Someone has control in his own life with qana’ah. Keywords: Qana’ah, Hamka, Mental Hygiene, Mental Health